2008
DOI: 10.1016/j.ejvs.2008.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Potential Circulating Biomarkers for Abdominal Aortic Aneurysm Expansion and Rupture - a Systematic Review

Abstract: Several circulating agents in peripheral blood may predict AAA size, expansion rate or rupture. Few of them have clinical potential for future use. Confirmative studies and development of multivariate models are needed, together with continuing search for new biomarkers using the discovery based sciences within proteomics and/or genomics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(36 citation statements)
references
References 45 publications
0
35
0
1
Order By: Relevance
“…Accordingly, there is a considerable body of work documenting hypothesis-based biomarker discovery investigations for AAA. This area has recently been reviewed,8,36,37,123 thus we will briefly discuss the techniques used to assess putative biomarkers and illustrate with appropriate examples.…”
Section: 0 Future Prospects Of Aaa Diagnosis and Monitoringmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, there is a considerable body of work documenting hypothesis-based biomarker discovery investigations for AAA. This area has recently been reviewed,8,36,37,123 thus we will briefly discuss the techniques used to assess putative biomarkers and illustrate with appropriate examples.…”
Section: 0 Future Prospects Of Aaa Diagnosis and Monitoringmentioning
confidence: 99%
“…In addition to this, the mural thrombus has been identified as a site for polymorphonuclear leukocyte accumulation and protease activation and release,29,32 suggesting that biochemical processes outside the arterial wall may contribute to AAA development. Several MMPs including MMP-1, -2, -3 and -9 have been proposed as putative markers for AAA 8,123. However, poor correlation between circulating MMP titres and vascular phenotype suggests that these are unreliable sentinels with which to stratify AAA patients 138140.…”
Section: 0 Future Prospects Of Aaa Diagnosis and Monitoringmentioning
confidence: 99%
“…All the references from the identified articles were searched for relevant information. The starting date was January 2008, since, previously, bibliography was covered by the review of Urbonavicius et al [17] and the end date of the review was April 2014. We focused on human studies that reported the presence of aneurysm, size, expansion rates, and risk of rupture and on new biomarkers and their potential value relevant to the management of AAA.…”
Section: Methodsmentioning
confidence: 99%
“…It is known that this risk increases when the observed expansion rate is greater than the expected [16]. Furthermore, a biomarker could define the optimal surveillance intervals and possibly identify pathogenic pathways which could guide monitoring and treatment [17]. We should not fail to mention that, in order for a biomarker to be employed in modern healthcare system, its use should be cost-effective.…”
Section: Introductionmentioning
confidence: 99%
“…The infiltrates are also abundant with pro-inflammatory cytokines such as prostaglandin E2 (PGE2) and interleukin 6 (IL6) 13. Furthermore, concentrations of circulating cytokines, such as interferon γ, have been associated with AAA expansion and rupture 14. Many factors may initiate the inflammatory response.…”
Section: Pathophysiology Of Aaa Growthmentioning
confidence: 99%